2015
DOI: 10.1002/pat.3703
|View full text |Cite
|
Sign up to set email alerts
|

Structure, morphology, and properties of LDPE/sepiolite nanofiber nanocomposite

Abstract: Sepiolite (SEP) nanofibers have been modified by grafting with poly(pentaerythritol diphosphonate dichloridehexamethylendiamine) (PSPHD) and compounded with low density polyethylene (LDPE) to form a nanocomposite. The various modified SEPs were characterized by X-ray photoelectron spectroscopy, Fourier transform infrared, transmission electron microscopy (TEM), and thermogravimetric analysis. The Fourier transform infrared and X-ray photoelectron spectroscopy tests show that covalent bonding exists between SEP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…The other part of coordinated water in SEP was removed between 400°C and 650°C. At 800°C, the last step of SEP dehydration occurred, which led to the destruction of SEP structure and the formation of enstatite (MgSiO 3 ) and silica 13,30 . Finally, the neat SEP had a total mass loss of about 13.3% in the temperature range of 40–800°C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The other part of coordinated water in SEP was removed between 400°C and 650°C. At 800°C, the last step of SEP dehydration occurred, which led to the destruction of SEP structure and the formation of enstatite (MgSiO 3 ) and silica 13,30 . Finally, the neat SEP had a total mass loss of about 13.3% in the temperature range of 40–800°C.…”
Section: Resultsmentioning
confidence: 99%
“…SEP is rich in Si and Mg and has a unique nanofibrous structure, which makes it possible to be a potential flame retardant or reinforcing agent. Moreover, hydroxyl groups on the surface of fibrous SEP particles are highly active and can be functionally modified before preparing nanocomposites 13,14 . Previous studies found that SEP could act as a synergistic agent in intumescent formulations by catalyzing the char‐forming reaction and improving the strength of the protective char layer 15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…Sepiolite, Mg 8 Si 12 O 30 (OH) 4 (H 2 O) 4 .8H 2 O, is a layered hydrated magnesium silicate with a needle‐like morphology and a high‐specific surface area (200‐300 m 2 /g) . It is an efficient reinforcing filler for some polymers and blends like polyamide‐6, PP, high density polyethylene, low density polyethylene, polyurethane, poly(sulphone ether imide), PLA/low density polyethylene blend, PLA/polycaprolactone blend, PLA/PP blend, PLA/natural rubber blend, and PLA, too . Liu et al reported that traditional modification of sepiolite is unnecessary because modified sepiolite deteriorate thermal properties of PLA.…”
Section: Introductionmentioning
confidence: 99%
“…For Sep, the four mass-loss events have a maximum loss at 70 °C, 261 °C, 495 °C, and 802 °C, with respective mass-loss percentages of 0.96%, 3.32%, 2.98%, and 2.60%. Sep has the same attributes as Pal, and the clay minerals are differentiated by the temperatures and percentages of loss in each event [23,24].…”
Section: Resultsmentioning
confidence: 99%